Energy cane: a revolutionary clean energy crop for the transition to a sustainable energy system - Sizuo Matsuoka (Academia Environmental Sciences and Sustainability)
The balance between food and energy is a significant global debate, with climate issues as an important backdrop. Agriculture has much to do with this debate, as it produces food to meet the needs of our ever-growing population and also delivers part of the highly desirable renewable energy. Among many prospective resources in the area of green energy, the Saccharinae clade, including sugarcane, is considered the most suitable. In this context, unlike traditional sugarcane, a distinct form called energy cane is more productive and highly resilient, i.e., it can better withstand stressful conditions compared to the sugarcane crop and can even thrive in them. The foundation for this performance is its fiber content: the higher its concentration in the plant, the more resilient it is. The traditional sugarcane industry has established the value of 12 ± 2% fiber as the ideal for the milling process, and all centuries-old breeding programs worldwide conform their cultivars to this paradigm. However, if this fiber concentration favors the industry, the field pays a penalty: the cultivars do not have enough resilience to thrive satisfactorily. As result, field productivity in Brazil and elsewhere has reached a stagnant plateau. Energy cane can change this scenario. The proposal is to adopt a form of energy cane with an intermediary fiber level workable by the mills (called Type I) and with enough sucrose content to make either sugar or ethanol. This pragmatic and innovative attitude will not only push up the yield plateau significantly but will also open the possibility of exploiting poor soil and water-limited soil areas with more efficiency and environmental sustainability. No less importantly, it will stimulate biorefineries and other side industries to produce a wealth of goods and chemicals, i.e., the once-monolithic sugarcane industry will be transformed into a multi-product conglomerate, increasing its profitability and adding social and environmental benefits to society.